"Filmičnost" literarnega diskurza Miljenka Jergovića - Benjak, Mirjana (Slavistična revija, 2000)
The approach to the volume of short stories Mama Leone by a Croatian author from the younger generation, Miljenko Jergovic, derives from the hypothesis that the influence of the mass media, particularly film, extends to the literary discourse. The article examines those forms of cinenatic recording that appera to be the essential structural elements of Jergović's stories, i.e., frames, camera positions, and montage.
Keywords: film; hrvaška književnost; Jergovič, Miljenko: Mama Leone